2016
DOI: 10.1186/s12889-016-3488-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing health literacy in the eastern and middle-eastern cultures

Abstract: BackgroundHealth literacy is a term employed to assess the ability of people to meet the increasing demands related to health in a rapidly evolving society. Low health literacy can affect the social determinants of health, health outcomes and the use of healthcare services. The purpose of the study was to develop a survey construct to assess health literacy within the context of regional culture. Different socioeconomic status among the Eastern and Middle Eastern countries may restrict, health information acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 23 publications
0
46
0
Order By: Relevance
“…Overall health literacy score was determined by aggregating correct answers from all questions and Research article ranged between 0 and 20. Scores were then categorized into 3 groups: inadequate (< 10), moderate (10)(11)(12)(13)(14) and adequate (> 14). Independent variables included age, sex, education, residence and occupation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall health literacy score was determined by aggregating correct answers from all questions and Research article ranged between 0 and 20. Scores were then categorized into 3 groups: inadequate (< 10), moderate (10)(11)(12)(13)(14) and adequate (> 14). Independent variables included age, sex, education, residence and occupation.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient health literacy levels vary greatly across different settings, varying from 54.3% in Germany to 58% in Turkey and 28.5% in England (9)(10)(11). Lower levels of health literacy are often observed in developing settings such as the Middle Eastern context (12). In the Islamic Republic of Iran, one of the most populated countries in the Middle East, several studies have tried to measure health literacy and reported overall insufficient health literacy levels, ranging from 41% in adults in the central province of Yazd to 68% in the southeastern province of Baluchistan (13).…”
Section: Introductionmentioning
confidence: 99%
“…Less than 3% of UAE females are illiterate, compared with 6% illiteracy rate among Emirati males, and about 30% illiteracy rate among Arab women. 25 UAE's inclusive education system has facilitated the emergence of female Emiratis who not only outperform their male fellow citizens educationally but also outperform females from other Middle East and North African nations where cultural norms still put females at a disadvantage vis-à-vis access to quality education. 27 As the UAE and other Gulf Cooperation Council nations' health systems progresses into the digital age, the need for highly health literate citizens cannot be over-emphasized if optimal returns on impressive investments in health are to be realized.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 To the best of our knowledge, this is the first study to systematically examine health literacy among adolescents in the Middle East and North Africa region. Unfortunately, a recently proposed instrument for assessing health literacy in this region, the Eastern-Middle Eastern Adult Health Literacy (EMAHL13) screening instrument 25 , focusses mainly on comprehension, but not numeracy, an important skill in health promotion and disease management. The survey participants in our research study in schools, where English is the main language of instruction and any difficulty in understanding the survey questionnaire was clarified by two of the authors (ZA & AA) who personally administered the survey.…”
Section: Discussionmentioning
confidence: 99%
“…Although in the Middle East and North African (MENA) region countries a number of studies have been carried out to investigate HL measures [17][18][19][20], among older adults and patients with chronic diseases [18], as well as the determination of HL [21], few studies have previously investigated the contribution of different socio-demographic factors to HL, and the associations between gender and HL in the region. Also, a majority of previous studies has only investigated the associations between sociodemographic characteristics and HL.…”
Section: Introductionmentioning
confidence: 99%